2008
DOI: 10.1210/en.2007-0313
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 2 Receptor Stimulation Increases the Rate of NG108–15 Cell Migration via Actin Depolymerization

Abstract: Angiotensin II (Ang II) has been reported to induce migration in neuronal cell types. Using time-lapse microscopy, we show here that Ang II induces acceleration in NG108-15 cell migration. This effect was antagonized by PD123319, a selective AT2 receptor antagonist, but not by DUP753, a selective AT1 receptor antagonist, and was mimicked by the specific AT2 receptor agonist CGP42112. This Ang II-induced acceleration was not sensitive to the inhibition of previously described signaling pathways of the AT2 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…However, it remains to be clarified as to how and whether AT2 receptors direct the differentiation of c-kitþAT2þ cells into cardiomyocytes and/or noncardiomyocytes. Given the fact that the AT2 receptor has a stimulating role in cell migration [27,28] and MI-induced production of BM c-kitþAT2þ cell pool was observed in the present study, it appeared that AT2 receptor-mediated mobilization/migration of BM c-kitþAT2þ cells into the infarcted myocardium may contribute to an increase in cardiac ckitþAT2þ cell population following AT2 receptor activation.…”
Section: Discussionmentioning
confidence: 47%
“…However, it remains to be clarified as to how and whether AT2 receptors direct the differentiation of c-kitþAT2þ cells into cardiomyocytes and/or noncardiomyocytes. Given the fact that the AT2 receptor has a stimulating role in cell migration [27,28] and MI-induced production of BM c-kitþAT2þ cell pool was observed in the present study, it appeared that AT2 receptor-mediated mobilization/migration of BM c-kitþAT2þ cells into the infarcted myocardium may contribute to an increase in cardiac ckitþAT2þ cell population following AT2 receptor activation.…”
Section: Discussionmentioning
confidence: 47%
“…This function in lung stromal fibroblasts may be a potential modulator of tumor susceptibility in chemical carcinogen-induced lung tumorigenesis [9]. NG108-15-induced AT2R stimulation increases cell migration via actin depolymerization by cofilin, and these are potentially new targets of AT2R signaling in the context of cellular migration [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Ang II type 2 receptor may improve synaptic plasticity through effects on ionic channel activity, since AT2R activation decreases T-type calcium channel activity, increases K + channel activity (Kang et al, 1992, 1993; Buisson et al, 1995), and alters actin cytoskeleton dynamics (Kilian et al, 2008). …”
Section: Linking Signaling and Function: Always A Difficult Challenge!mentioning
confidence: 99%
“…Indeed, several studies have reported that AT2R activates PP2A phosphatase (Huang et al, 1995, 1996a,2008; Kilian et al, 2008). PP2A is markedly deficient in AD, and responsible for a sustained increase in ERK1/ERK2, one of the kinases involved in glycogen synthase kinase-3 (GSK-3) inactivation.…”
Section: Linking Signaling and Function: Always A Difficult Challenge!mentioning
confidence: 99%